Reviewing Materials Modification Techniques to Enhance the Durability of Surgical Scissors - mardina, zahrina (Liaison Journal of Engineering, 2023)
Around 22-33% of medical waste is contributed to the disposal of surgical tools. With over 310 million surgeries carried out annually, the burden of surgical tool waste becomes critical in terms of cost and effort in approaching zero net waste. Among the most common surgical waste is surgical scissors, often disposed of due to corroded surface, fracture, or loss of functionality. Since surgical scissors play such a major role in dissecting various organs, the reduced quality results in bleeding, uneven cutting, and contusion and enhances the risk of site infection. One way to reduce the amount of surgical waste is by enhancing durability achieved by applying surface modifications, such as coating. This paper reviews three surface modification approaches for surgical scissors coating, namely (1) anodized coating, (2) thin metallic glasses, and (3) chemical vapor deposition. Some experimental data from the reported studies were summarized to assess the potential methods to enhance surgical scissors' durability and reduce medical waste. Keywords: surgical scissors; durability; medical waste; CVD, thin metallic glasses. Anodized aluminum.